Tingkat Pengetahuan, Sikap, dan Perilaku Remaja tentang Kesehatan Reproduksi di SMK Negeri 8 Medan - Nasution, Iqbal Pahlevi Adeputra; Manik, Binsyah Sari Indah Gajah (SCRIPTA SCORE Scientific Medical Journal, 2020)
Background: Reproductive health is one of the most important things for human life, which includes a complete physical, mental, social welfare condition in all matters relating to the function and role of the reproductive system. Reproductive health education should be given since adolescence, because adolescence is a phase towards more mature reproduction. Adolescent problems related to reproductive health, often stem from a lack of information, understanding and awareness to achieve reproductive health. Objectives: This study aims to determine the level of knowledge, attitudes and behavior of adolescents about reproductive health at SMK Negeri 8 Medan. Methods: This study was a descriptive study with a cross sectional design. The research data is primary data, namely by filling out a questionnaire. The sample of this research is 96 people. The sample technique is stratified random sampling. Data were analyzed using the SPSS computer program using descriptive statistical tests and displaying the results in distribution and frequency tables. Results: Knowledge level of adolescents in SMK Negeri 8 Medan is good (59.4%), attitude level is good (80.2%) and behavior level is good (99%). Conclusion: The level of knowledge, attitudes and behavior of adolescents about health reproduction at SMK Negeri 8 is classified as good. Keywords: adolescent, attitude, behavior, knowledge, reproductive health Â  Â  Latar Belakang: Kesehatan reproduksi merupakan salah satu hal yang sangat penting bagi kehidupan manusia yaitu mencakup keadaan sejahtera baik fisik, mental, sosial yang utuh dalam segala hal yang berkaitan dengan fungsi, peran dari sistem reproduksi. Pendidikan kesehatan reproduksi sebaiknya diberikan sejak remaja, karena remaja merupakan fase menuju reproduksi yang lebih matang. Permasalahan remaja yang berkaitan dengan kesehatan reproduksi, sering kali berakar dari kurangnya informasi, pemahaman dan kesadaran untuk mencapai keadaan sehat secara reproduksi. Tujuan: Penelitian ini bertujuan untuk mengetahui tingkat pengetahuan, sikap dan perilaku remaja tentang kesehatan reproduksi di SMK Negeri 8 Medan. Metode: Penelitian ini adalah studi deskriptif dengan desain cross sectional. Data penelitian adalah data primer yaitu dengan pengisian kuesioner. Sampel penelitian ini berjumlah 96 orang. Teknik sampel adalah stratified random sampling. Data dianalisis menggunakan program komputer SPSS menggunakan uji statistik deskriptif dan menampilkan hasil dalam tabel distribusi dan frekuensi. Hasil: Tingkat pengetahuan remaja SMK Negeri 8 Medan tergolong baik (59,4%), tingkat sikap tergolong baik (80,2%), dan tingkat perilaku tergolong baik (99%). Kesimpulan: Tingkat pengetahuan, sikap dan perilaku remaja tentang kesehatan reproduksi di SMK Negeri 8 tergolong baik. Kata kunci: kesehatan reproduksi, pengetahuan, perilaku, remaja, sikap